REDUCING HABITUAL CLASS TARDINESS - Y. Hughes, Diane (European Scientific Journal, ESJ, 2014)
This article is intended to offer professors an alternative solution tothe increasing occurrence of late arriving students. At any given time it is notusual that at least five to ten percent of the enrolled students will enter theclass after the professor has started the lecture. While arriving late in the pastmay have been viewed as irresponsible, today students often feel entitled todo so. This article describes a technique used to reduce student tardiness andpossibly improve class performance.